Mengurai Kembali Peta Perkembangan Agama Hindu di Bali dan Nusantara - I Made Pasek Subawa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
The development of Hinduism in the archipelago, especially in Bali, originated from the teachings of the Vedas which were then translated into various forms of lontar literature. The lontar work which is a development of the Vedas written in accordance with local culture makes it easier for them to understand religious teachings so that this library is then used as a reference for them to believe in Hinduism. With this understanding, it shows that the development of the Hindu religious teaching system in the archipelago and Bali in particular is a derivative of the Vedic understanding which is rewritten in various lontars containing ideas and ideas according to the culture of the people. This is then the basis for Hinduism that is flexible and naturalistic that can be accepted in the religious system in the archipelago.